2008
DOI: 10.1123/jtpe.27.2.138
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Outcomes of a Responsibility-Based Physical Activity Program Integrated into an Intact High School Physical Education Class

Abstract: Underserved youth are at risk for numerous threats to their physical and psychological well-being. To navigate the challenges they face, they need a variety of positive life skills. This study systematically explored the implementation and short-term outcomes of a responsibility-based physical activity program that was integrated into an intact high school physical education class. Qualitative methods, drawing on multiple data sources, were used to evaluate a 20-lesson teaching personal and social responsibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(79 citation statements)
references
References 34 publications
2
70
0
7
Order By: Relevance
“…Similarly Hellison (2003) emphasized that building character is synonymous with personal and social development that includes learning to take responsibility for self and towards others. Various scholars have reported positive findings in the response of students to involvement of the Personal and Social Responsibility model (see for example, Wright and Burton 2008;Wright, Rukavina, and Pickering 2008). Although character has been defined in many ways and is often assumed to be synonymous with personality, it is not surprising then that moral character has been used as a phrase to depict an expected outcome for sport participation, and by implication, for physical education as well, in the social and moral domain 1 .…”
Section: Introductionmentioning
confidence: 94%
“…Similarly Hellison (2003) emphasized that building character is synonymous with personal and social development that includes learning to take responsibility for self and towards others. Various scholars have reported positive findings in the response of students to involvement of the Personal and Social Responsibility model (see for example, Wright and Burton 2008;Wright, Rukavina, and Pickering 2008). Although character has been defined in many ways and is often assumed to be synonymous with personality, it is not surprising then that moral character has been used as a phrase to depict an expected outcome for sport participation, and by implication, for physical education as well, in the social and moral domain 1 .…”
Section: Introductionmentioning
confidence: 94%
“…However, it has been shown that if teachers, and those supporting their professional learning through MBP, are creative and willing to experiment (Wright and Burton 2008) then positive changes can be made in the spaces where physical education is taught. However, as the next section shows these changes do not occur without some compromises.…”
Section: Change For Teachersmentioning
confidence: 99%
“…Only a few studies have implemented the TPSR model through school based physical education classes, as in the case of Wright and Burton (2008). That study aimed to systematically explore the implementation and short-term outcomes of a responsibility-based physical activity program that was integrated into an intact high school physical education class.…”
mentioning
confidence: 99%